Old Age and the Decline in Financial Literacy - Finke, Michael S.; Howe, John S.; Huston, Sandra J. (Management Science, 2017)
Households age 60 and older bear increasing responsibility for managing retirement portfolios, and they hold the majority of financial assets in the United States. Cognitive aging studies find evidence of a decline in fluid and crystallized intelligence in old age that may impact the ability to manage money effectively. Using a large sample of older respondents, we test whether knowledge of basic concepts essential to effective financial choice declines after age 60. We find a consistent linear decline in financial literacy score after age 60. A nearly identical rate of decline among men, stockowners, older, and college-educated respondents indicates that cohort effects are not driving the results. Confidence in financial decision-making abilities does not decline with age. A separate analysis using data that include measures of cognitive ability suggests that a natural decline in both fluid and crystallized intelligence in old age contributes to falling financial literacy scores. This paper was accepted by Brad Barber, finance.